The Test Stand Load Modulus Implementation for the Realistic Railway Operation in the Laboratory Conditions - Gerlici, Juraj; Lack, Tomáš; Harušinec, Jozef (Manufacturing Technology Journal, 2013)
The aim of the article is to present the necessity of completion of the test stand of brake components of railway vehicles with the equivalent railway operation load simulator for the research of the wheel wear on it. The other aim of presented research needs is to perform the analysis of the equivalent conicity as a parameter for the rail vehicles in operation ride properties prediction. The sub aims are the change of frame, wheel, braking forces load via SIMRAIL simulator program load collection performance.
Keywords: test stand; railway operation; laboratory conditions; wheel tread wear; equivalent conicity